2018
DOI: 10.1126/science.aan1053
|View full text |Cite
|
Sign up to set email alerts
|

Locally translated mTOR controls axonal local translation in nerve injury

Abstract: How is protein synthesis initiated locally in neurons? We found that mTOR (mechanistic target of rapamycin) was activated and then up-regulated in injured axons, owing to local translation of mTOR messenger RNA (mRNA). This mRNA was transported into axons by the cell size-regulating RNA-binding protein nucleolin. Furthermore, mTOR controlled local translation in injured axons. This included regulation of its own translation and that of retrograde injury signaling molecules such as importin β1 and STAT3 (signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
196
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 225 publications
(210 citation statements)
references
References 51 publications
6
196
0
Order By: Relevance
“…This would explain the downregulation observed from T3 to T14 and the subsequent upregulation at T21, when axons regenerate. Whether L-Pgds mRNA is locally translated in injured axons as it occurs for other proteins is not known (Koley, Rozenbaum, Fainzilber, & Terenzio, 2019;Spaulding & Burgess, 2017;Terenzio et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This would explain the downregulation observed from T3 to T14 and the subsequent upregulation at T21, when axons regenerate. Whether L-Pgds mRNA is locally translated in injured axons as it occurs for other proteins is not known (Koley, Rozenbaum, Fainzilber, & Terenzio, 2019;Spaulding & Burgess, 2017;Terenzio et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Though not always mechanistic, several high-throughput surveys of mRNAs in neural tissues have revealed that APA in brain results in longer 3 0 UTRs than other tissues (Fontes et al, 2017;Miura, Shenker, Andreu-Agullo, Westholm, & Lai, 2013). In neurons, longer 3 0 UTRs often result in selective translation of those mRNA isoforms in dendrites and axons (Ainsley, Drane, Jacobs, Kittelberger, & Reijmers, 2014;Terenzio et al, 2018) or reveal distal last exons that can localize transcripts to neurites (Taliaferro et al, 2016). We also believe that techniques like c-Tag-PAPERCLIP, in which epitope tags can be attached to RNA-binding proteins of interest in specific mouse cell types (Hwang et al, 2017), will increase the understanding of APA in brain and other tissues.…”
Section: Splicing and Polyadenylation Control Cgrp Expressionmentioning
confidence: 99%
“…This suggests additional cytoplasmic and axonal functions for these RBPs in post-mitotic neurons, perhaps due to the much greater expanses of cytoplasm that neurons must grow and sustain with their long axonal processes. Multifunctionality has been documented for several RBPs, including axonal ZBP1, FMRP, nucleolin, and HuD that contribute to transport and stability or transport and translation of neuronal mRNAs (6,(51)(52)(53)(54). Both the RIP-seq data and depletion studies point to functions in axonal growth for hnRNP H1, F, and K. It will be of high interest to determine the molecular mechanisms for growth promotion by these hnRNPs and distinguish nuclear and somatic vs. axonal functions for these proteins.…”
Section: Sj Lee Et Al Rna-protein Interactions For Axonal Mrnasmentioning
confidence: 99%